1981
DOI: 10.1136/hrt.46.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Relation between admission time, haemodynamic measurements, and prognosis in acute myocardial infarction.

Abstract: SUMMARY Pulmonary arterial end-diastolic pressure, cardiac index, and stroke work index were measured via a thermistor-tipped balloon catheter and monitored for 51±51 hours in 226 patients admitted with an acute myocardial infarction (184 survivors and 42 non-survivors). Mortality was related to time of admission after onset of symptoms of infarction. Of 69 patients in group A 13 died in hospital (18 8%) one to four hours after onset; in group B (five to eight hours after onset) eight of 71 patients (11%) died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 25 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that patients with congestive heart failure complicating acute myocardial infarction have poor prognosis [5][6][7][8][9]. Even in the thrombolytic era, left ventricular dysfunction remains the single most important predictor of mortality following acute myocardial infarction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that patients with congestive heart failure complicating acute myocardial infarction have poor prognosis [5][6][7][8][9]. Even in the thrombolytic era, left ventricular dysfunction remains the single most important predictor of mortality following acute myocardial infarction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…1) and longer term ( fig. 2) mortality risk is concentrated in those with haemodynamic evidence of heart fail ure [3][4][5][6][7][8]. For these reasons the treatment of left ventricular failure complicating acute myocardial infarction demands urgent atten tion and aggressive correction.…”
mentioning
confidence: 99%